A Novel Solution for Distal Dilation of Chronic Dissection After Repair Involving Visceral Branches: The Road Block Strategy - Li, Yiming; Li, Zhenjiang; Feng, Jiaxuan; Feng, Rui; Zhou, Jian; Jing, Zaiping (Frontiers in Cardiovascular Medicine, 2022)
Aim Notwithstanding that unprecedented endovascular progress has been achieved in recent years, it remains unclear what is the best strategy to preserve the blood perfusion of abdominal visceral arteries and promote positive aortic remodeling in patients with distal dilatation of chronic aortic dissection in abdominal visceral part (CADAV) after aortic repair. The present study developed a Road Block Strategy (RBS) to solve this conundrum. Methods and Results This prospective single-center clinical study included patients suffering from symptomatic distal dilatation of CADAV after aortic repair treated with RBS from January 2015 to December 2019 and followed up regularly for at least 2 years. Stent grafts were implanted first to cover distal tears and expand the true lumen. Device embolization was performed to induce proximal and distal segmental false lumen thrombosis (FLT) apart from the level of the ostia of vital branches. Successful RBS was performed in 13 patients. Significant differences were found in maximum true lumen diameter (p < 0.05), blood flow area in false lumen (FL) (p < 0.001), and the ratio of blood lumen to FL area (p < 0.05) between the pre-procedure and the latest follow-up results. No aortic rupture, vital branches occlusion, thoracic and abdominal pain, or death occurred during hospitalization and follow-up. Conclusions Our findings suggest that RBS is feasible in treating distal dilatation of chronic aortic dissection after prior proximal repair, inducing false lumen thrombosis, preventing deterioration of aortic dissection, and maintaining the patency of abdominal visceral arteries.